Prevalence and Prognostic Significance of Hyponatremia in Patients With Lung Cancer: Systematic Review and Meta-Analysis - Bartalis, Eszter; Gergics, Marin; Tinusz, Benedek; Földi, Mária; Kiss, Szabolcs; Németh, Dávid; Solymár, Margit; Szakács, Zsolt; Hegyi, Péter; Mezösi, Emese; Bajnok, László (Frontiers in Medicine, 2021)
Background: The prevalence of hyponatremia is highly variable among patients with lung cancer. However, its prevalence and prognostic significance in subgroups of patients with lung cancer have not yet been evaluated in a meta-analysis. Methods: We have registered our meta-analysis and review protocol to the PROSPERO International Prospective Register of Systematic Reviews, with the following registration number: CRD42020167013. A systematic search was done in the following sources: MEDLINE, Embase, CENTRAL, Web of Science, ClinicalTrials.gov, a WHO Global Health Library. Results: We identified a total of 8,962 potentially eligible studies, and we included 31 articles in our evaluation. The prevalence of hyponatremia in patients with lung cancer varied between 3 and 94.8% with an average of 25% without any significant differences between the following subgroups: histotype, gender, age, Eastern Cooperative Oncology Group (ECOG) state, and the extent of disease. The overall survival (OS) was significantly lower in hyponatremic compared to normonatremic patients at 10 months [RR.59 (95% CI.47–0.74), p < 0.001] and at 20 months [RR.44 (95% CI.33–0.59), p < 0.001], with worse survival rates in non-small cell lung cancer (NSCLC) [RR.27 (95% CI.12–0.44), p < 0.001] than in small cell lung cancer (SCLC) [RR.42 (95% CI.27–0.57), p < 0.001]. If hyponatremia was corrected, OS at 10 months was significantly higher than in the uncorrected hyponatremia group [RR 1.83 (95% CI 1.37–2.44), p < 0.001], but, at 20 months, no statistically significant difference could be found between these subgroups [RR 2.65 (95% CI.94–7.50), p = 0.067]. Conclusions: Patients with lung cancer diagnosed with hyponatremia, especially patients with NSCLC, seem to have significantly lower survival rates than normonatremic patients. If hyponatremia remains uncorrected, the mortality rates might be even higher.